The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/20543581211027759
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Acute Kidney Injury in Patients Admitted to Hospital With COVID-19: A Retrospective Cohort Study

Abstract: Background: The incidence of acute kidney injury (AKI) in patients with COVID-19 and its association with mortality and disease severity is understudied in the Canadian population. Objective: To determine the incidence of AKI in a cohort of patients with COVID-19 admitted to medicine and intensive care unit (ICU) wards, its association with in-hospital mortality, and disease severity. Our aim was to stratify these outcomes by out-of-hospital AKI and in-hospital AKI. Design: Retrospective cohort study from a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As of Oct. 31, 2023, the main results of 12 of the 16 RCTs 20-28 (75%) and 4 of the 7 cohort studies [29][30][31][32][33] (57.1%) had been published. References and citation metrics appear in Appendix 1, Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…As of Oct. 31, 2023, the main results of 12 of the 16 RCTs 20-28 (75%) and 4 of the 7 cohort studies [29][30][31][32][33] (57.1%) had been published. References and citation metrics appear in Appendix 1, Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30 , 31 ] However, in our cohort, we only found it associated with increasing age. Now concerning the presentation, Pitre et al [ 32 ] gave their aspect of 57.6% of patients presented with AKI to the hospital, while the rest 42.4% developed AKI during in-hospital stay. Furthermore, these in-hospital events can be attributed to the disease course, development of cytokine release storm, [ 33 ] or drug-induced renal injury related to COVID-19 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Chan et al reported lower incidence in Chinese provinces like Guangdong (1.74%), Hong Kong (3.72%), and Hubei (4.25%), but very high in American states like Michigan (44.73%), New York (33.07%) and Pennsylvania (49.33%) [ 17 ]. Similarly, other Western Pacific nations like Singapore (8.1%) and South Korea (4.0%) also reported low rates [ 4 , 18 ], compared to Middle Eastern countries (Iran 37.6%, Bahrain 47.6%) [ 19 , 20 ], Europe (Italy 22%, UK 29%, Turkey 54%, Portugal 55%) [ 21 - 24 ] and the Americas (USA 33-49%, Brazil 71%, Canada 54%) [ 6 , 7 , 25 , 26 ]. The wide discrepancies are likely related to dissimilarities in handling the pandemic through different screening and admission policies, healthcare disparities, hospital capacity, surveillance systems, social determinants, and disease epidemiology.…”
Section: Discussionmentioning
confidence: 99%